2018
DOI: 10.1308/rcsann.2018.0053
|View full text |Cite
|
Sign up to set email alerts
|

Removing a metal foreign object successfully from a patient’s retroperitoneal space using laparoscopy and a novel navigation system

Abstract: Trauma with foreign objects retained within the human body has become a common surgical emergency condition. Traditional surgical methods often involve creating large incisions in soft tissue and may lead to additional complications during wound healing. We have developed a new method of removing foreign bodies from patients' abdomens by using laparoscopy with the help of a novel navigation system that provides accurate positioning. This approach is minimally invasive and simple. This is the first combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…However, up to 10% needs removal and majority of them can be retrieved successfully through endoscopic intervention. Only 1% of these FB may need some form of surgical intervention 1,6 . The peak incidence of FB ingestion occurs between 6 months and 6 years of age 5 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, up to 10% needs removal and majority of them can be retrieved successfully through endoscopic intervention. Only 1% of these FB may need some form of surgical intervention 1,6 . The peak incidence of FB ingestion occurs between 6 months and 6 years of age 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is primarily made on history and during information gathering, the clinician can reach the nature of diagnostic evaluation, urgency, type and extent of a possible surgical intervention. Two plain radiographs of the affected body area have been recommended as a part of initial assessment and are very helpful if FB is radio-dense 6,15 . Mosca et al 14 reported confirmed diagnosis of ingested FB in 38% of their patients on basis of plain x-ray alone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations